The Growth of Oil Palm (Elaeis guineensis Jacq.) Seedlings with the Application of Different Arbuscular Mycorrhiza Fungi and Various Phosphorous Dosages - Krisnarini Krisnarini; Maria Viva Rini; Paul Benyamin Timotiwu (UNIVERSITY OF LAMPUNG, 2018)
The effectiveness of Arbuscular Mycorrhiza Fungi (AMF) colonization depends on the type of AMF, plant species and phosphorus fertilization. The aims of this study were to determine: the best type of AMF and the appropriate dosage of P fertilizer for the growth of oil palm seedlings, and whether the oil palm seedling responses to the application of AMF type is determined by the dosage of phosphorus applied. The experiment was arranged in a Randomized Complete Block Design (RCBD) with two factors and 5 replications. The first factor was the types of AMF (m), consisting of without mycorrhiza inoculation (m0), Gigaspora sp. MV16 isolate (m1), Glomus sp. MV7 isolate (m2), Gigaspora sp. MV16 isolate + Glomus sp. MV7 (m3) isolate. The second factor was phosphorus fertilization (SP-36), consisting of 3 levels: 1/3 recommended dosage (p1), 2/3 recommended dosage (p2), full recommended dosage (p3). The results showed that the application of all AMF types resulted in the same effects on the growth of oil palm seedlings, however the seedling growth in the inoculated plants were better than in uninoculated plants (control). The application of the recommended dosage of P fertilizer produced the highest seedling growth. The response of seedlings to the application of AMF type was not determined by doses of phosphorus fertilizer applied.